Application of high-pressure and ultrasound technologies for legume proteins as wall material in microencapsulation: New insights and advances. (September 2022) - Sridhar, Kandi; Bouhallab, Saïd; Croguennec, Thomas; Renard, Denis; Lechevalier, Valérie
Abstract: Background: Plant proteins, especially legume proteins, are among the most versatile, nutritious, and sustainable protein sources compared to animal-derived counterparts. Moreover, legume proteins have recently attracted interest of the scientific community owing to their wall-forming, gelling, and emulsifying properties in microencapsulation delivery systems. However, many industries have limited the use of legume proteins due to their poor solubility, lower functionality, presence of saponins and phenols leading to beany favor, and susceptibility to environmental stress. Modification of legume protein functional properties through emerging high-pressure and ultrasound technologies have therefore attracted considerable research interests to prepare legume proteins with desirable functional properties as wall material. Scope and approach: This article reviews recent studies on the application of emerging technologies to modify legume protein functional properties for the improvement in encapsulation properties. The application of legume protein-based microcapsules in the design of novel foods and their bioavailability is thoroughly discussed with an emphasis on the current scientific knowledge and future perspective. Key findings and conclusions: The review highlighted the growing interest on legume proteins due to consumer shift towards healthy diet choices that also have a better ecological footprint. The legume protein-based market has gained momentum among the consumer market with USD 267.53 million over 2019 to 2023, which is ultimately due to growing preference for sustainable and healthier foods. Application of non-thermal technologies, such as high-pressure and ultrasound technologies to legume proteins significantly improved their structure, functionality, and other encapsulation properties to better encapsulate the bioactive core materials. The designed novel foods using microencapsulated bioactive compounds with legume proteins showed the increased bioavailability of active components along with controlled release, improved nutritional values, sensory attributes, and other health-promoting effects. Graphical abstract: Image 1 Highlights: Legume proteins are clean-green sources for microencapsulation applications. High-pressure and ultrasound improve the legume protein functional properties. Legume proteins can be applied in microencapsulation as wall materials. Legume protein market continues to skyrocket in global plant-based protein market. Pea and soy proteins are among the prominent sources in the legume protein market.